The construction of a system of open spaces for Colatina, ES - Simões, Renata Mattos; Mendonça, Eneida Maria Souza (Farol, 2025)
This article presents the results of descriptive and analytical research on the open space system in the municipality of Colatina, Espírito Santo, focusing on the relationship between the distribution, type, and quantity of open spaces in the territory, territorial planning, and the ecological potential for connecting these spaces. The issues raised by the research are linked to the way open spaces are addressed in urban planning legislation and how the creation of a system could improve the quality of the urban environment. Based on the principles of landscape ecology, the study suggests a methodology for classifying open spaces and creating a system that prioritizes connections between open spaces, stimulates ecological flow and ecosystem recovery, and contributes to the improvement of the urban environment.
Keywords: Open space system; urban rivers; urban evolution; landscape ecology; urban spatial planning